Causes and consequences of crude oil pipeline vandalism in the Niger delta region of Nigeria: a confirmatory factor analysis approach - Umar, Ahmed Tukur; Othman, Moh’d Shahwahid (Taylor and Francis, 2017)
Significant number of crude oil pipeline vandalism in the Niger delta region of Nigeria were carried out by the militant groups on the pretext for a better environmental management and development of the region. This research work examined the relation between socioeconomic, institutional factors and pipeline vandalism using confirmatory factor analysis (CFA). The CFA is a superior model of analysis since it establishes a better mathematical relationship between observed and unobserved variables compared to other models previously used by other studies such as correlation analysis, ordinary least squares and descriptive statistics. The study involved 269 respondents who were selected from the Niger delta region using purposive and simple random sampling techniques. The results from the study show the existence of a significant and positive relationship between poor management, poor governance, legal, and environmental degradation while significant but negative relationship between marginalization and pipeline vandalism. The study recommends the need for institutional reform through improvement in infrastructural provision, effective governance among others. Unlike other previous studies, our results show no significant relationship between poverty, unemployment and vandalism.